Proceso contable y su incidencia en la rentabilidad de la asociación de producción agropecuaria Guasaganda “ASOPAGUA”, del cantón La Maná, provincia de Cotopaxi, en el periodo 2017-2018. - Guarochico Herrera, Yessenia Estefanía (2019)
The research project entitled "Accounting process and its impact on the profitability of the Guasaganda Agricultural Production Association" ASOPAGUA ", of La Maná, Cotopaxi province, in the period 2017-2018" identified in simple terms that the problem is framed in the deficient preparation of the financial statements, since they do not correctly perform the accounting process due to lack of information, this has caused an imbalance in the organization. In view of the aforementioned problem, the need arose to draw up a solution proposal that would be implemented as a corrective measure in the Association, contributing to improve the economic, financial and accounting situation, generating trust for members, employees, workers and other people who benefit with the development of their activities. A survey was conducted that was aimed at the active members of the Association and an interview with the current accountant, in order to propose a model of accounting process that is applied within the organization, so that it has a better control of the operations that they do day by day, resulting in the feasibility of the research as there is a commitment from the people who are part of the collection center to reduce the existing shortcomings, to improve the current situation of the organization, through an alternative solution that implies the correct elaboration of the accounting process that must be carried out, in order to obtain reliable and true financial statements. The impact of the project is positively established within the “ASOPAGUA” Agricultural Association, because by implementing a good accounting process, it directly contributes to the recognition, measurement, registration and correct presentation of the transactions carried out by the organization, besides it needs timely and reasonable financial statements that contain true information, thus demonstrating the current situation in which the entity is, this for proper management and decision making that contributes to the emergence and progress of it.